Photopyroelectric spectroscopy of polyaniline films - De Albuquerque, J. E.; Melo, W. L.B. [UNESP]; Faria, R. M. (My University, 2000)
Photopyroelectric spectroscopy (PPES), in the 400<λ<900 nm wavelength range, was used to study thermal properties of differently doped polyaniline (PAN) films. The photopyroelectric intensity signal Vn(λ) and its phase Fn(λ) were independently measured, as well as the intensity Vn(f) and the phase Fn(f) (f being the chopping frequency) for a given λ of the saturation part of the PPES spectrum. Equations of both the intensity and the phase of the PPES signal, taking into account the thermal and the optical characteristics of the PAN films and the pyroelectric detector, were used to fit the experimental results. From the fittings we obtained, with great accuracy, the values of thermal conductivity κ and thermal diffusivity coefficient α of PAN films of different doping degrees. It was observed that, in contrast with the strong doping-dependence of the electrical conductivity, the thermal parameters of PAN films remained practically unchanged under doping. This apparent discrepancy is explained by the granular metal model of doped PAN.